Anxiety and Extraversion in Lupus-Related Atherosclerosis - Giannelou, Maira; Tseronis, Dimitrios; Antypa, Eleni; Mavragani, Clio P. (Frontiers in Psychiatry, 2018)
Objectives: Patients with systemic lupus erythematosus (SLE) are characterized by increased cardiovascular disease (CVD) risk as well as heightened rates of psychological distress. Since a link between psychological issues and CV morbidity has been previously suggested, the influence of psychological burden on subclinical atherosclerosis in SLE patients was investigated. Methods: 71 SLE patients were assessed for the presence of subclinical atherosclerosis -defined either as carotid and/or femoral plaque formation or arterial wall thickening [Intima Media Thickness (IMT) levels>0.90mm by Doppler ultrasound]; personality traits, anxiety and depression, sleeping habits and fatigue levels were also evaluated by specific questionnaires including Eysenck Personality Questionnaire Scale, State-Trait Anxiety Inventory (STAI), Zung Depression Scale, Athens Insomnia Scale and Functional Assessment of Chronic Illness Therapy-Fatigue (FACIT-F). Disease related clinical and laboratory features and traditional risk factors for atherosclerosis were documented. Univariate and multivariate analysis were performed. Results: SLE patients with arterial wall thickening displayed higher STAI anxiety scores (either as a current state or as a personality trait) compared to those without (49.8±5.6 vs 46.9 ±5.4, p-value: 0.03 and 49.2±4.4 vs 45.7±6.8, p-value:0.009, respectively). In a multivariate model, trait anxiety and extraversion personality scores were found to be independently associated with arterial wall thickening and plaque formation, respectively [OR95%(CI):1.2(1.0-1.5) and 0.7(0.6-1.0), respectively], following adjustment for potential confounders. No other associations were detected. Conclusions: Anxiety and extraversion personality traits have been independently associated with subclinical atherosclerosis in lupus patients, implying psychoneuroimmunological interactions as contributors in SLE related atherosclerosis.